Advancing Alzheimer’s Diagnosis: The Role of AI - A Review - Dominka Rehan; Sven Solisch; Anna Blazhkova; Anna Susłow; Adam Szwed; Ewa Szczęsna (Journal of Education, Health and Sport)
Introduction: Alzheimer's disease (AD) is a progressive neurodegenerative disease that accounts for more than half of all cases of dementia worldwide. An aging society therefore poses a huge challenge to medicine. The exact mechanism responsible for this disease is still not fully understood. However, theories of neurodegeneration related to the deposition of pathological proteins in the brain and the imbalance between individual neurotransmitters have allowed the development of effective diagnostic methods - laboratory determination of specific biomarkers (tau protein, β-amyloid) and their marking using PET (Amyloid PET, Tau PET). Magnetic resonance imaging (MRI) is also important in diagnostics. Artificial intelligence (AI) is a promising, new, and rapidly developing path that can significantly affect the diagnostic process of Alzheimer's disease.